A coupled thermo-mechanical model based on the combined finite-discrete element method for simulating thermal cracking of rock. (January 2017) - Yan, Chengzeng; Zheng, Hong
Abstract: Based on a combined finite-discrete element method (FDEM), this study builds a coupled thermo-mechanical model (termed FDEM-TM) to simulate thermal cracking of rock. The coupled thermo-mechanical model consists of two major parts. In the first part the temperature distribution of the system is analyzed based on the heat conduction equation. In the second part the thermal stress caused by temperature change is added to perform mechanical fracture calculation. Based on these two parts, we can model rock fracture driven by thermo-mechanical coupling. Three examples with analytic solutions are used to verify the correctness of the model in dealing with the problems of steady-state heat conduction, unsteady-state conduction, and thermal-mechanic coupling, respectively. In addition, an example of thermal cracking is also given and compared with the experimental results. The simulation results are in excellent agreement with the analytical solutions or experimental results, verifying the correctness of the coupled thermo-mechanical model to simulate thermal cracking. The proposed method provides a new tool for thermal-mechanical coupling problems in geothermal exploitation. Highlights: An FDEM-based model, FDEM-TM, is proposed for simulating thermal cracking of rock. FDEM-TM is able to describe thermal-mechanic behaviors in rock. The proposed method provides a new way for thermal-mechanical coupling problems in geothermal exploitation.